Impact of Momordica charantia (karela) on serum alanine aminotransferase level in streptozotocin induced diabetic rats - Mohal, S; Mondal, DK; Chowdhury, PK; Biswas, H; Khanom, A; Shamim, KM (Mediscope, 2015)
The present experimental study was conducted at Department of Anatomy in BSMMU (Bangabandhu Sheikh Mujib Medical University) & BIRDEM (Bangladesh Institute of Research & rehabilitation in Diabetes, Endocrine & metabolic Disorders) to investigate whether Momordica charantia (karela) has got any impact on serum alanine aminotransferase (ALT) level in the streptozotocin-induced diabetic rats. Sixty healthy young Long Evans rats of male sex weighing 150 to 280 gm aged between 10 to 12 weeks were used in this study. The rats were divided into 4 equal groups depending on their different sorts of dietary feedings and drug treatment. The final ALT level (on 51st day) ranged from 23 to 34 u/L (mean 30.10 u/L) in healthy rats, 56 to 80 u/L (mean 68.50 u/L) in the untreated diabetic rats, 36 o 37 u/L (mean 31.50 u/L) in the insulin-treated diabetic rats and 61 to 96 u/L (mean 81.10 u/L) in the karela-treated diabetic rats. The ALT percentage change value of diabetic rats on 51st day corresponding to the initial on 7th day was significantly higher than that healthy rats (p<0.001). The value in the insulin-treated diabetic rats was significantly lower than that of the untreated diabetic rats (p<0.001) & the karela-treated diabetic rats (p<0.001). There was no significant difference between the values of the untreated diabetic rats & the karela-treated diabetic rats (p>0.05). The present study did not show that karela has any significant impact of acting against higher serum ALT level in streptozotocin-induced diabetes mellitus. Further investigation is recommended for establishing karela as an agent against higher serum ALT level in diabetes mellitus. DOI: http://dx.doi.org/10.3329/mediscope.v1i1.21634 Mediscope Vol. 1, No. 1: 2014, Pages 29-32